Effect of Drying Duration on Water Content and Ash Content of Red Salak Fruit (Salacca edulis) Herbal Tea - Smith, Alwi; Pattiasina, Eifan Boyke; Simal, Rufiati; Karepesina, Fitriah Husna; Raharusun, Ayu Ningsih; Baysi, Asmawati Rahma (Universitas Brawijaya, 2024)
Negeri Riring, Taniwel District, West Seram Regency, Maluku Province, has many agricultural opportunities for red salak. Salak is unique with thick, dark yellow flesh with a red tinge, which is why it is called red snake fruit. Currently, the red salak plant is only used for its fruit flesh; the skin and other parts of the plant are immediately removed and disposed of in the environment. Red salak fruit skin, which has high antioxidant and polyphenol content, can be utilized and processed into new products, such as herbal tea. Drying is an important stage in the process of making herbal tea. Making herbal tea from red salak fruit skin is carried out in the Biology Laboratory. The aim of this research is to determine how long drying impacts water and ash content. The research method used was an experiment using a simple Completely Randomized Design (CRD), namely at the same temperature, namely 60°C and with a long drying treatment. The Ambon Industrial Standardization and Services Center tests water and ash content. Analysis of variance (ANOVA) was used to analyze research data at a confidence level of 5%. The results showed that the drying time had a significant impact on the water content, but did not have a significant impact on the ash content of the red salak fruit rind herbal tea.